Sex After Life Essays on Extinction, Vol. 2 - Colebrook, Claire (Critical Climate Change, 2014)
Sex After Life aims to consider the various ways in which the concept of life has provided normative and moralizing ballast for queer, feminist and critical theories. Arguing against a notion of the queer as counter-normative, Sex After Life appeals to the concept of life as a philosophical problem. Life is neither a material ground nor a generative principle, but can nevertheless offer itself for new forms of problem formation that exceed the all too human logics of survival.